Neutrophils Are Dysregulated in Patients with Hereditary Angioedema Types I and II in a Symptom-Free Period - Grymova, Tereza; Vlkova, Marcela; Soucek, Premysl; Hakl, Roman; Nechvatalova, Jana; Slanina, Peter; Stichova, Julie; Litzman, Jiri; Freiberger, Tomas (Mediators of inflammation, 2019)
Neutrophils impact on processes preceding the formation of bradykinin, a major swelling mediator in hereditary angioedema (HAE), yet their potential role in HAE pathogenesis has not been sufficiently studied. We assessed the relative mRNA expression of 10 genes related to neutrophil activation using RNA extracted from the peripheral blood neutrophils of 23 HAE patients in a symptom-free period and 39 healthy donors. Increased relative mRNA expression levels of CD274, IL1B, IL1RN, IL8, MMP9, and TLR4, together with a lack in their mutual correlations detected in HAE patients compared to healthy controls, suggested a preactivated state and dysregulation of patients' neutrophils. Patients' neutrophil-alerted state was further supported by increased CD11b, decreased CD16 plasma membrane deposition, and increased relative CD274+ and CD87+ neutrophil counts, but not by increased neutrophil elastase or myeloperoxidase plasma levels. As CD274 mediates inhibitory signals to different immune cells, neutrophils were cocultured with T-cells/PBMC. The decrease in CD25+ and IFN-γ + T-cell/PBMC ratio in patients indicated the patients' neutrophil suppressive functions. In summary, the results showed neutrophils' alerted state and dysregulation at the transcript level in patients with HAE types I and II even in a symptom-free period, which might make them more susceptible to edema formation. Neutrophils' T-cell suppressive capacity in HAE patients needs to be further investigated.
Keywords: Peroxidase; Interleukin-1beta; Humans; messenger RNA; toll-like receptor 4; dítě; Receptors, Urokinase Plasminogen Activator; Hereditary Angioedema Types I and II; Child; antigeny CD11b; pankreatická elastasa; dospělí; mladý dospělý; Interleukin-8; ELISA; Leukocytes, Mononuclear; Toll-Like Receptor 4; interleukin-8; neutrofily; peroxidasa; receptory urokinázového aktivátoru plazminogenu; hereditární angioedém, typy I a II; lidé; Cells, Cultured; Interleukin 1 Receptor Antagonist Protein; B7-H1 Antigen; Enzyme-Linked Immunosorbent Assay; Adult; RNA, Messenger; receptory IgG; Matrix Metalloproteinase 9; Receptors, IgG; Flow Cytometry; interleukin-1beta; kultivované buňky; matrixová metaloproteinasa 9; Adolescent; Neutrophils; Pancreatic Elastase; Young Adult; leukocyty mononukleární; průtoková cytometrie; CD11b Antigen; antigeny CD274; antagonista receptoru pro interleukin 1; mladiství